Determination of the enantiomeric and diastereomeric impurities of RS‐glycopyrrolate by capillary electrophoresis using sulfated‐β‐cyclodextrin as chiral selectors. Issue 23 (2nd October 2014) - Zuo, Lihua; Zhao, Yunfeng; Ji, Fenfen; Zhao, Min; Jiang, Zhen; Sun, Tiemin; Guo, Xingjie
<x xml:space="preserve">Abstract</x> A practical chiral CE method, using sulfated‐β‐CD as chiral selector, was developed for the enantioseparation of glycopyrrolate containing two chiral centers. Several parameters affecting the separation were studied, including the nature and concentration of the chiral selectors, BGE pH, buffer type and concentration, separation voltage, and temperature. The separation was carried out in an uncoated fused‐silica capillary of (effective length 40 cm) × 50 μm id with a separation voltage of 20 kV using 30 mM sodium phosphate buffer (pH 7.0, adjusted with 1 M sodium hydroxide) containing 2.0% w/v sulfated‐β‐CD at 25°C. Finally, the method for determining the enantiomeric impurities of RS‐glycopyrrolate was proposed. The method was further validated with respect to its specificity, linearity range, accuracy and precision, LODs, and quantification in the expected range of occurrence for the isomeric impurities (0.1%).